(untitled) (Journal of Partial Differential Equations, 1994)
We will establish an existence and regularity theory for weak solutions of a class of singular parabolic equations associated with Dirichlet data, whose prototype is u_t - div(|&#8711u|^p-2&#8711u) = 0 (1 < p < 2)